IMPLEMENTASI PROGRAM SEKOLAH RAMAH ANAK DALAM PROSES PEMBELAJARAN - Fahmi, Agus (Prodi Administrasi Pendidikan, Universitas Pendidikan Mandalika, 2021)
There were 241 cases of violence against children recorded until November 10th 2020. The Office of Women's Empowerment and Child Protection of NTB Province carries out its obligations to protect and fulfill children's rights by trying to protect, save, and provide protection to children from discrimination, violence, and ensuring their right to grow and develop. The government then initiates and runs the Child Friendly School Program. Facts in the field based on initial observations, at State Elementary School 8 Sokong has implemented a child-friendly school program which is becoming an example for other schools. The objectives of this study are (1) to describe the planning for the implementation of the child-friendly school program, (2) to describe the implementation of the Child Friendly School Program, (3) To describe the results of the monitoring and evaluation of the implementation of the Child Friendly School Program at State Elementary School 8 Sokong.This study is a descriptive qualitative research. The data collection used are observation, interview, and documentation. The data obtained validated using source triangulation. The data then analyzed since the data collected, namely data reduction, data presentation, and drawing conclusions and verification. The results of the research show that (1) The Child Friendly School Program planning has fulfilled the program SOP, namely by forming a development team who construct program activity plan. (2) The program implementation has met the program indicators by being implemented without violence and discrimination against child. (3) Monitoring is carried out by providing previously prepared questionnaires to be filled out by school principals and representatives of educators and education staff, then monitored by relevant agencies and institutions. Meanwhile, the evaluation of the program implemented at State Elementary School 8 Sokong was evaluated in its entirety along with other programs.Keywords: Child-friendly School, Learning.